2022
DOI: 10.3389/fnut.2022.953012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of conjugated linoleic acid supplementation on lipid profile in adults: A systematic review and dose–response meta-analysis

Abstract: BackgroundThe findings of trials investigating the effect of conjugated linoleic acid (CLA) administration on lipid profile are controversial. This meta-analysis of randomized controlled trials (RCTs) was performed to explore the effects of CLA supplementation on lipid profile.MethodsTwo authors independently searched electronic databases including PubMed, Web of Science, and Scopus until March 2022, in order to find relevant RCTs. The random effects model was used to evaluate the mean and standard deviation.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…132 A meta-analysis found that dietary supplementation of CLA significantly improved HDL-C concentration but increased the concentrations of TG, TC, LDL-C, apolipoprotein A, and apolipoprotein B. 133 Moreover, some researchers have also attempted to compare the health benefits of CLnA and CLA toward CVD. For example, Franczyk-Z ̇aroẃ et al 134 compared the antiatherosclerotic effects of CLnA (PA) and CLA (c9, t11-CLA), and the results showed that, although PA was beneficial for lipid metabolism, it did not have the same effect as CLA in reducing the formation of atherosclerosis in the whole aorta.…”
Section: Antidiabetic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…132 A meta-analysis found that dietary supplementation of CLA significantly improved HDL-C concentration but increased the concentrations of TG, TC, LDL-C, apolipoprotein A, and apolipoprotein B. 133 Moreover, some researchers have also attempted to compare the health benefits of CLnA and CLA toward CVD. For example, Franczyk-Z ̇aroẃ et al 134 compared the antiatherosclerotic effects of CLnA (PA) and CLA (c9, t11-CLA), and the results showed that, although PA was beneficial for lipid metabolism, it did not have the same effect as CLA in reducing the formation of atherosclerosis in the whole aorta.…”
Section: Antidiabetic Effectsmentioning
confidence: 99%
“…However, there are data that suggest CLA treatment can cause ventricular tachyarrhythmias (VT) in mice and lead to death during myocardial infarction (MI), so individuals at risk of myocardial infarction should consume CLA with caution . A meta-analysis found that dietary supplementation of CLA significantly improved HDL-C concentration but increased the concentrations of TG, TC, LDL-C, apolipoprotein A, and apolipoprotein B . Moreover, some researchers have also attempted to compare the health benefits of CLnA and CLA toward CVD.…”
Section: Biological Activity and Health Function Advantagesmentioning
confidence: 99%
“…CLA have been investigated for various beneficial effects, including cancer, atherosclerosis and obesity (13)(14)(15)(16) . Major isomers of CLA are cis-9, trans-11 CLA (9, 11 CLA) and trans-10, cis-12 CLA (10, 12 CLA) (17) , which are found naturally in ruminant animal food products (18) and are primary components of widely consumed CLA weight-loss supplements (19,20) . Although humans can produce endogenous CLA, the blood and tissue levels of CLA in non-supplemented individuals are less (21,22) .…”
mentioning
confidence: 99%